2021
DOI: 10.1186/s12864-021-08182-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome resequencing of three Coilia nasus population reveals genetic variations in genes related to immune, vision, migration, and osmoregulation

Abstract: Background Coilia nasus is an important anadromous fish, widely distributed in China, Japan, and Korea. Based on morphological and ecological researches of C. nasus, two ecotypes were identified. One is the anadromous population (AP). The sexually mature fish run thousands of kilometers from marine to river for spawning. Another one is the resident population which cannot migrate. Based on their different habitats, they were classified into landlocked population (LP) and sea population (SP) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Among the annotated outliers, there were also four genes with potential links to migratory behaviour (CACNB3-, OR2K2-, OR56A4-, and SLCO1C1-like). The calcium channel subunit CACNB3 is associated with the annotated outlier locus with the highest F ST between the ecotypes, and has previously been linked with migratory phenotypes in fish (Cao et al ., 2020; Gao et al ., 2021). The two olfactory receptors OR2K2 and OR56A4 are located within a cluster of olfactory genes on chr 16, and olfaction is heavily involved in establishing long-term memory and homing behaviour in fish (Hara, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Among the annotated outliers, there were also four genes with potential links to migratory behaviour (CACNB3-, OR2K2-, OR56A4-, and SLCO1C1-like). The calcium channel subunit CACNB3 is associated with the annotated outlier locus with the highest F ST between the ecotypes, and has previously been linked with migratory phenotypes in fish (Cao et al ., 2020; Gao et al ., 2021). The two olfactory receptors OR2K2 and OR56A4 are located within a cluster of olfactory genes on chr 16, and olfaction is heavily involved in establishing long-term memory and homing behaviour in fish (Hara, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge suggests that the migratory behaviour of fish, such as anadromy in salmonids, results in selective pressure on genomic regions associated with olfaction and sensory perception in general (Gao et al, 2021 ). The above is most likely due to the fact that navigation for natal homing of migrating individuals relies on the detection and processing of environmental stimuli such as odours (Bett & Hinch, 2016 ; Døving et al, 1985 ; Ueda et al, 2016 ; Wisby & Hasler, 1954 ; Yamamoto et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [18] showed that the oocytes in the ovaries of C. nasus at all developmental stages had obvious synchronization and belonged to the type of one-time spawning, and the ovaries could be divided into six developmental stages from I to IV. Recently, more studies have been conducted on the metabolic mechanisms [19], immunity [20,21], energy utilization [22][23][24], and key regulatory pathways in the liver and brain [25] during the reproductive migration of C. nasus, while relatively few studies have been conducted on factors related to ovarian development. In this study, we investigated the changes in the factors related to the reproductive development of C. nasus at the hormone and gene levels.…”
Section: Introductionmentioning
confidence: 99%